2009
DOI: 10.5194/hess-13-551-2009
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on Blue Nile flows using bias-corrected GCM scenarios

Abstract: Abstract. This study analyses the output of 17 general circulation models (GCMs) included in the 4th IPCC assessment report. Downscaled precipitation and potential (reference crop) evapotranspiration (PET) scenarios for the 2081-2098 period were constructed for the upper Blue Nile basin. These were used to drive a fine-scale hydrological model of the Nile Basin to assess their impacts on the flows of the upper Blue Nile at Diem, which accounts for about 60% of the mean annual discharge of the Nile at Dongola. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
148
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(159 citation statements)
references
References 30 publications
9
148
1
1
Order By: Relevance
“…The headwater starts at Lake Tana in the Ethiopian highlands, and most of the flow originates from a large number of downstream tributaries. The river has cut a deep canyon through the highlands and drains a large portion of western Ethiopia (Elshamy et al, 2009). Elevations range from $4000 m in the Ethiopian highlands to $500 m at the EthiopiaSudan border.…”
Section: Study Areamentioning
confidence: 99%
“…The headwater starts at Lake Tana in the Ethiopian highlands, and most of the flow originates from a large number of downstream tributaries. The river has cut a deep canyon through the highlands and drains a large portion of western Ethiopia (Elshamy et al, 2009). Elevations range from $4000 m in the Ethiopian highlands to $500 m at the EthiopiaSudan border.…”
Section: Study Areamentioning
confidence: 99%
“…Daily meteorological data such as temperature and precipitation were collected from the Ministry of Water Resources and Electricity and other different sources for the period (Beyene et al, 2010;Taye et al, 2011;Enyew et al, 2014;Gebre et al, 2015). The MIROC-ESM and CCSM4 (Jury, 2015) models similarly have been selected (Elshamy et al, 2009;Beyene et al, 2010;Setegn et al, 2011). However, for CCSM4, there is a clear difference in rainfall trend (base period) in some months.…”
Section: Datamentioning
confidence: 99%
“…The climate change in the Upper Blue Nile basin has been addressed by many previous studies using different climate models and techniques (Elshamy et al, 2009;Beyene et al, 2010;Taye et al, 2011;Setegn et al, 2011;Enyew et al, 2014;Gebre et al, 2015). The Dinder River (DR) is one of the largest tributaries of the Blue Nile River and a major water resource in the Dinder National Park (DNP).…”
Section: Introductionmentioning
confidence: 99%
“…[5] used two conceptual hydrological models that were calibrated and used to carry out climate change impact assessment for two future Special Report on Emissions Scenario (SRES) A1B and B1 for 2050s using 17 GCMs for Nile basin. The result of the study has showed that there is unclear trend (like [9] and [10]) in Lake Tana sub-basin for projected flows (mean and high/low) and this is mainly attributed to Global Climate Models (GCMs) uncertainty.…”
Section: Introductionmentioning
confidence: 99%